2011
DOI: 10.1177/1099636211400130
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of thermo-mechanical properties of transversely flexible sandwich panels by functionally graded skins

Abstract: In this article bending response of the sandwich panel with functionally graded (FG) skins under thermal and/or mechanical loading is studied. Higher order sandwich plate theory has been exploited. In addition, by using Fourier conduction equation and obtaining temperature distribution, thermo-elastic behavior of such structure is investigated. Comparison between the results of analytical and FEM solutions is indicative of robustness of the analytical solution for prediction of in-plane and out-of-plane stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The effect of the uncertainty in the elastic properties of the laminated and sandwich composite structure and subsequent nonlinear eigenvalue solutions are reported by Chandrashekhar and Ganguli [31]. The effect of thermomechanical loading effect on the flexural and buckling behaviour of the FG sandwich plate structure investigated using [32][33]. As discussed earlier, the HSDT kinematics is further utilised to model the and sandwich and laminated composite panel to compute the static and the dynamic behaviour by Mantari et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the uncertainty in the elastic properties of the laminated and sandwich composite structure and subsequent nonlinear eigenvalue solutions are reported by Chandrashekhar and Ganguli [31]. The effect of thermomechanical loading effect on the flexural and buckling behaviour of the FG sandwich plate structure investigated using [32][33]. As discussed earlier, the HSDT kinematics is further utilised to model the and sandwich and laminated composite panel to compute the static and the dynamic behaviour by Mantari et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…Woodward and Kashtalyan [5] analyzed a three-dimensional elasticity for a sandwich panel with stiffness of the core graded in the thickness direction, on the basis of the developed 3D elasticity solution subjected to distributed and concentrated loadings. In [610], the bending and post-buckling of sandwich FGM structures with FGM core were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Sadighi et al. 59 studied bending response of a sandwich panel with functionally graded skins under thermal and/or mechanical loading using higher order sandwich plate theory and Fourier conduction equation to obtain temperature distribution and then investigate thermoelastic behaviour of such structure. They showed that wise selection of FG skin materials is helpful to decrease the delamination failure possibility under thermo mechanical loading.…”
Section: Introductionmentioning
confidence: 99%
“…Kheirikhah and Khalili 58 presented an accurate finite element model for bending analysis of softcore rectangular sandwich plates with orthotropic homogeneous core and graded skins in the ANSYS 11.0 standard code area. Sadighi et al 59 studied bending response of a sandwich panel with functionally graded skins under thermal and/or mechanical loading using higher order sandwich plate theory and Fourier conduction equation to obtain temperature distribution and then investigate thermoelastic behaviour of such structure. They showed that wise selection of FG skin materials is helpful to decrease the delamination failure possibility under thermo mechanical loading.…”
Section: Introductionmentioning
confidence: 99%